Design model of computerized personal decision aid for youth: An expert review - Sarif, Siti Mahfuzah; Ibrahim, Norfiza; Shiratuddin, Norshuhada (2016)
This paper provides a structured review of a design model of a computerized personal decision aid that is intended for youth, named as YouthPDA Design Model. The proposed design model was examined by experts in related areas to ensure the appropriateness of the proposed components and elements, relevancy of the terminologies used, logic of the flow, usability, and practicality of the design model towards development of YouthPDA application. Seven experts from related areas were involved in the evaluation. Discussions on the findings obtained from the expert review are included in this paper. Finally, a revised design model of YouthPDA is proposed as main guidance to develop YouthPDA application.